Sébastien Chauvin, Peter Clegg and Bruno Cousin (2018, eds.), Euro-Caribbean Societies in the Twentieth Century. Offshore Finance, Local Elites and Contentious Politics, Abingdon and New York: Routledge - Godfrey Baldacchino (Partecipazione e Conflitto, 2019)
For Book Reviews Abstract is not Required